Upaya Pemberdayaan Istri Nelayan Desa Karangjaladri Kabupaten Pangandaran Melalui Produk Olahan Ikan Bilis - Nora Akbarsyah; Luthfi Thirafi; Farisadri Fauzan (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2023)
Amid Indonesia's large fishery potential, groups of small fishermen who play a role in this sector face uncertainty and unresolved welfare problems. This can be found in Bojong Salawe Hamlet, Karangjaladri Village, Pangandaran Regency. The fishing families of Bojong Salawe Hamlet only depend on the sale of fish without adding much-added value to their catch. There's a need for an activity that encourages the fishing families of Karangjaladri Village to process their catches. This activity begins with the observation process, followed by product research and demonstrations as well as product processing training. Based on survey data, the knowledge and skills of the community, especially fishermen's wives, towards fish processing are fairly good, so the manufacture of processed products is not difficult. The processing of wilis fish that can be made into chili sauce has very good potential as an alternative income, as a job opportunity, and also as a typical processed product of Karangjaladri Village, Bojongsalawe Hamlet, especially for fishing families in this region.